2005
DOI: 10.1002/pola.21194
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of poly(1,3‐cyclohexadiene): Influence of the polymer chain structure

Abstract: The influence of the microstructure on the oxidation of poly(1,3‐cyclohexadiene) (PCHD) homopolymer, obtained by anionic polymerization with alkyllithium/amine systems, was investigated for the first time. PCHD has a structure consisting of a main chain formed by 1,2‐addition (the 1,2‐CHD unit) and 1,4‐addition (the 1,4‐CHD unit). The molar ratio of 1,2‐CHD/1,4‐CHD units in the polymer chain strongly influenced the extent of oxidation of PCHD. A polymer chain with a high content of 1,4‐CHD units was easily oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 22 publications
2
64
0
Order By: Relevance
“…In previous papers, [31,33,34] we revealed that the dehydrogenation of PCHD was strongly affected by the molar ratios of 1,2-CHD/1,4-CHD units. In addition, it was discovered that the degree of dehydrogenation could be controlled by the reaction conditions.…”
Section: Controlled Dehydrogenation Of Pchdmentioning
confidence: 97%
See 4 more Smart Citations
“…In previous papers, [31,33,34] we revealed that the dehydrogenation of PCHD was strongly affected by the molar ratios of 1,2-CHD/1,4-CHD units. In addition, it was discovered that the degree of dehydrogenation could be controlled by the reaction conditions.…”
Section: Controlled Dehydrogenation Of Pchdmentioning
confidence: 97%
“…As described in previous papers, [31,33,34] this dehydrogenation reaction is an aromatization; therefore, the extent of dehydrogenation for PCHD (conversion from 1,2-CHD and/or 1,4-CHD units to 1,2-phenylene (1,2-Ph) and/or 1,4-phenylene (1,4-Ph) units) can be estimated by a decrease in olefinic signals (Ho at ca. 5.7 ppm, 2H per CHD unit) and an increase in aromatic signals for the Ph units (Hp at ca.…”
Section: Controlled Dehydrogenation Of Pchdmentioning
confidence: 99%
See 3 more Smart Citations